Soles dermatoglyphics in the prognosis of sports endowment: differences of soles dermatoglyphics in sportsmen of different sport kinds - Lyshevska, V. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The problem of determining associations between certain groups of sports and dermatoglyphics feet. The study involved 207 men, the general population (those who are not in sports), aged 17-19 years and 78 men highly skilled athletes. It is shown that as a criterion in the sports orientation of children and adolescents can be dermatoglyphics. The features of the structure of the foot dermatoglyphics in men of different sports specialties. There are informative signs dermatoglyphics thumb and feet, which can be recommended to assess the prospects of a particular athlete's motor activity. Among these are the types of finger patterns, combined account and certain dermatoglyphic phenotypes. It is proved that certain features of dermatoglyphics feet act as genetic markers in predicting propensity athletes to realize the potential of high specific energy pattern.